Guadalcanal Marine - Lane, Kerry (Book collections on Project MUSE., 2004)
In Guadalcanal Marine, Kerry L. Lane recounts the dark reality of combat experienced by the men of the 1st Marine Division fighting on Guadalcanal and Cape Gloucester. With eighty gripping photographs and his text, he brings to life the struggles of his companions as they achieve these two astonishing victories. Lane, a sixteen-year-old farm boy from North Carolina, battled the Japanese and rose to heroism powering a bulldozer to bridge ""Suicide Creek"" in the swamps on Cape Gloucester. There he led his Marine comrades to victory. Lane describes the trials of the common Marine serving in